6.1. Zapisz dany wzór funkcji kwadratowej f w postaci f(x) = a * x ^ 2 + bx + c . Następnie wypisz współczynniki a, b, c. a) f(x) = 3x – 6x ^ 2 + 2(x ^ 2 – 1, 5x) c) f(x) = 2x ^ 2 + x(5pi – x) e) f(x) = (3x – 7) ^ 2 b) f(x) = x ^ 2 – 2(sqrt(2) * x ^ 2 + 4) d) f(x) = (4 – x)(4 + x) + 3(x – 1) f) f(x) = 2 – (x – sqrt(3)) ^ 2

6.1. Zapisz dany wzór funkcji kwadratowej f w postaci f(x) = a * x ^ 2 + bx + c . Następnie wypisz współczynniki a, b, c. a) f(x) = 3x – 6x ^ 2 + 2(x ^ 2 – 1, 5x) c) f(x) = 2x ^ 2 + x(5pi – x) e) f(x) = (3x – 7) ^ 2 b) f(x) = x ^ 2 – 2(sqrt(2) * x ^ 2 + 4) d) f(x) = (4 – x)(4 + x) + 3(x – 1) f) f(x) = 2 – (x – sqrt(3)) ^ 2